Generation of Nanodroplet Reactors and Their Applications in In Situ Controllable Synthesis and Transportation of Ag Nanoparticles - Lin, Guanhua (Adv Sci (Weinh), 2021)
Nanodroplets have been paid great attention as they are crucial for a wide range of physical, chemical, and biological applications. In this paper, monodispersed nanodroplets are prepared and their directed motions are realized through conducting the formation of nonuniform structures via altering the ionic distribution within; all these dynamics have been observed by using in situ transmission electron microscopy liquid cell technology. It has been found that their transformation from random motion to directed motion is reversible. Moreover, combining multiple directed motions enables long‐distance travel with directed motion taking up 95% of the total time. The results here also prove that aqueous nanodroplets can slide directionally on the hydrophilic surface like droplets sliding on hydrophobic surface. Furthermore, the authors successfully achieve the unidirectional transportation of in situ prepared Ag nanoparticles by using the nanodroplets as nanoreactor, carrier, and transporter. The size and number of as‐prepared Ag nanoparticles can be quantitatively controlled. In summary, this research provides a new strategy for real‐time generation and precise manipulation of aqueous nanodroplets. Together with the quantitatively controllable in situ synthesis of Ag nanoparticles within the nanodroplets, this work can prove their promising applications in many fields.